2003
DOI: 10.12938/bifidus1996.22.85
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects ofBifidobacterium longumon EnterohemorrhagicEscherichia coliO157: H7

Abstract: The effects of Bifidobacterium longum BB536 (BB536) on Escherichia coli O157:H7 IPH9 (IPH9) were first examined using germ-free mice mono-associated with BB536 (BB536-MA). Thirty-two days after oral challenge with a lethal dose of IPH9, all the non-associated germ-free mice (GF) died, but all the BB536-MA mice survived and the number of IPH9 in the feces was lower than that in GF mice. Second, co-culture experiments with BB536 and IPH9 were performed. The number of IPH9 in the co-culture was less than 1% of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In addition, lesions in the kidneys, but not in the intestines, were observed in GF Swiss Webster mice infected with EHEC (Eaton et al 2008). Previously, Aiba et al (2002) and Namba et al (2003) investigated E. coli O157:H7, using GF BALB/c mice. Namba et al (2003) reported that mild lesions were induced in the kidneys.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, lesions in the kidneys, but not in the intestines, were observed in GF Swiss Webster mice infected with EHEC (Eaton et al 2008). Previously, Aiba et al (2002) and Namba et al (2003) investigated E. coli O157:H7, using GF BALB/c mice. Namba et al (2003) reported that mild lesions were induced in the kidneys.…”
Section: Discussionmentioning
confidence: 97%
“…Previously, Aiba et al (2002) and Namba et al (2003) investigated E. coli O157:H7, using GF BALB/c mice. Namba et al (2003) reported that mild lesions were induced in the kidneys. They did not describe lesions in the intestines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also some reports that oral intake of probiotics can improve bowel movement disturbance such as diarrhea (Gismondo et al, 1999) and coprostasis (Fukushima et al, 2004;Yaeshima et al, 1997). In addition, probiotics have been reported to have a prophylactic effect against infectious diseases (Namba et al, 2003) and an ameliorating effect on inflammatory bowel diseases (Fukushima et al, 2004;Gionchetti et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Lactic acid bacteria including bifidobacteria produce acetic acid and/or lactic acid, which tend to lower the intestinal pH and thus inhibit the proliferation of pathogenic microorganisms (Collins and Gibson, 1999;Gomes and Malcata, 1999). Bifidobacterium longum is found mainly in human feces (Mitsuoka, 1982), as well as Lactobacillus acidophilus, and reported to have protective effects against harmful intestinal bacteria such as Escherichia coli (Ibrahim and Bezkorovainy, 1993;Kojima et al, 1995;Namba et al, 2003). On the other hand, some lactic acid bacteria have been used in the preservation of foods because of their inhibiting activity against food poisoning and spoilage bacteria such as Salmonella Typhimurium and Staphylococcus aureus (Raccach et al, 1979).…”
Section: Introductionmentioning
confidence: 99%